Clipping and Blending Words in Japanese Internet Slang: Philosophical Perspective - Meilantari, Ni Luh Gede; Aritonang, Betty (Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2024)
Philosophy is a system of thought or rather a way of thinking that can be challenged. Philosophy is also a process, a way of searching for truth indefinitely. The philosophy of science, on the other hand, is a philosophical study that seeks to answer questions about the nature of science in terms of ontology, epistemology, and axiology. More than two decades ago, the world was stunned by a new technology known as the internet. As the internet matures into a technology that connects the world, the number of internet-related languages grows. Similarly, in Japanese, there are many words that were created and are related to the internet. There are special internet terms in Japanese that arose as a result of borrowing from English terms. There are also those that arise as a result of the word process. Some internet-specific terms, such as web or bug, are derived from English vocabulary that predates the internet. However, in Japanese, the term has been adapted into a new vocabulary related to the internet. This paper is designed to highlight the particular forming new words through the process of blending and clipping. This paper also intends to highlight philosophical aspects. It investigates the use of blend words and clipping in Japanese internet slang. In terms of internet in Japanese, the blending process consists of a combination of Japanese (wago) and English (gairaigo) words from different or the same word classes. Blends created from word which belong to the different words classes, the interpretation of their meaning generally involved straightforward process. Keywords: Clipping, Blending, Japanese, Internet slang